Perbedaan Pengaruh Terapi SEFT Dan SPEOS Terhadap Kelancaran Produksi ASI antara Ibu Primipara dengan Multipara di RSUD Hanafie Bungo - Fitriwati, Citra Indah; Dwi, Hani Ruh (REAL in Nursing Journal, 2023)
Backround : Breastfeeding is one of the most effective ways to protect a mother's health while providing the best nutrition for the baby in her life. There are various ways that can be done to help increase breast milk production by using SEFT therapy (Spiritual Emotional Freedom Technique) and certain massage techniques, especially in the back area, such as the SPEOS Method (Endorphin, Oxytocin and Suggestive Massage Stimulation). Purpose : The aim of this research is to determine the difference between SEFT and SPEOS therapy on the smooth production of breast milk between primiparous and multiparous mothers at Hanafie Regional Hospital. Methods : This research uses a quasi-experimental method with a pre-post test design with a control group. This research was conducted in July-August 2023. The research population was all postpartum mothers at Hanafie Regional Hospital. The research sample consisted of 52 people. Data analysis used the Independent T-test. Results : The results of the research show the characteristics of this study where most of the postpartum mothers were aged 20-35 years with a presentation of 29.6% while primiparous women, 20-35 years with a presentation of 27.8%. After statistical tests using the Independent T-Test based on the results of the posttest in the intervention group (the group that was given SEFT and SPEOS therapy) showed a p value = 0.001. Conclusion: there was a significant difference in average breast milk production between primiparas and multiparas in the intervention group.Keywords :  SEFT, SPEOS, Exclusive breastfeeding, Primiparous, Multiparous